A fuzzy multi-criteria approach for evaluating the contribution of freight transportation towards India's Nationally Determined Contributions (NDCs). Issue 9 (3rd May 2021) - Mahapatra, Diptiranjan; Katiyar, Rajesh; Parida, Ratri; Kumar, Divesh
Abstract : Adoption of the Paris Agreement in December 2015 and its subsequent ratification through Nationally Determined Contribution (NDC) marked, among other things, India's commitment to reduce the emission intensity of its GDP by 33–35 per cent by 2030 from 2005 level. The transport sector, being the prime conduit of production value-chain, has been a major contributor to global energy-related greenhouse gas (GHG) emissions. In this context, it is critical production research study that needs to evaluate the linkage of NDC with freight transport. The proposed framework consists of goal setting, seeking expert opinion and driving insights into the field of freight transport. First, goal and criteria or attribute for achieving NDC through the freight sector are identified. Next, expert opinions from transport and climate change specialists are sought. Lastly, results and insights related to the most feasible alternatives, such as heavy road, heavy rail, hybrid, heavy waterborne, and heavy air with regard to the select attributes and its sub-attributes viz, slower growth, structural changes in sector and economy, strategic and operational choices, technology and innovation and regulatory and economic instruments with the help of fuzzy analytic hierarchy process (FAHP) are drawn. The strength of the proposed methodology is that it uses FAHP to prescribe definitive solutions to climate change policymakers and logistics and supply chain managers who otherwise would have found difficulties with such an arcane subject having partial and little quantified information.